Continuous High-Dose (6 mg) vs. Low-Dose (3 mg) Intravitreal Ganciclovir for Cytomegalovirus Retinitis After Haploidentical Hematopoietic Stem Cell Transplantation: A Randomized Controlled Study - Chen, Wei-Bin; Long, Ze; Hou, Jing; Miao, Heng; Zhao, Ming-wei (Frontiers in Medicine, 2021)
Purpose: To evaluate the safety and efficacy of continuous high-dose (6 mg) intravitreal ganciclovir injections (IVG) for cytomegalovirus (CMV) retinitis (CMVR) after haploidentical hematopoietic stem cell transplantation (Haplo-HSCT), and to explore factors that may influence the treatment procedure. Design: Prospective, randomized, single-blinded, positive-controlled, interventional, comparative study. Methods: A total of 22 patients with CMVR (32 eyes) were randomized to either high-dose group (IVG 6 mg weekly) or low-dose group (IVG 3 mg given twice weekly for 2 weeks as induction phase and weekly thereafter as maintenance phase). Patients who were recorded any positive CMV DNAemia or other active CMV diseases and needed systemic anti-CMV treatment during the study period were excluded. The vision outcome, variables of the treatment procedure, and incidence of complication and CMVR recurrence were analyzed and compared. Logistic regression was applied to determine the factors that may have an impact on the treatment process at baseline. Results: Compared to the low-dose group, the high-dose group resulted in a median of two less intravitreal injections (4 vs. 6 times, respectively, P = 0.016), while the rate of vision stability or improvement (81.2 vs. 87.5%), the incidence of complication (6.2 vs. 18.8%), and CMVR recurrence (12.5% vs. 6.2%) were similar (all P > 0.05). No drug-related toxicity was observed. Initial aqueous CMV-DNA load (OR: 6.872, 95% CI: 1.335–35.377, P = 0.021) and extension of lesion (OR: 0.942, 95% CI: 0.897 to .991, P = 0.020), but not dosing regimen (P = 0.162), were predictors of the treatment duration. Conclusions: Continuous high-dose regimen was well tolerated and resulted in less intravitreal injections, with similar vision outcomes and safety profiles. The clinical course of CMVR after Haplo-HSCT was determined by its own nature at baseline and could not be modified by treatment protocols under consistent immune background.